Recovery sequence of Picea mariana – Vaccinium uliginosum forests after burning near Inuvik, Northwest Territories, Canada - Black, R. Alan; Bliss, Lawrence C. (Canadian Journal of Botany, 1978)
Picea mariana – Vaccinium uliginosum vegetation was sampled in a north–south transect near Inuvik, N.W.T., Canada. Four stages in the postfire recovery sequence were described. Little qualitative change in vascular plants was found in the transect or with time since burning, although quantitative changes were found to exist. Contrary to vascular plant development, an orderly postfire succession of cryptogamic species was found. The postfire recovery sequence by comparison with other open boreal forest studies has a persistent shrub-dominated stage. Burning, with few exceptions, occurred within 100 years of examination along the transect. Objective analyses by Bray–Curtis ordination and reciprocal averaging ordination were used to analyse the vegetation data and proved useful in the data reduction and interpretation of results.